ANALISIS HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KEMANDIRIAN PERSONAL HYGIENE PADA ANAK USIA PRA SEKOLAH DI DUSUN CELEGEH DESA BAREBALI LOMBOK TENGAH TAHUN 2019 - Yulianti Yulianti; Amalia Mastuty; Edy Surya Pratama (LPPM STIKES Muhammadiyah Kendal, 2019)
The role of parents as caregivers and the response from the enviroment is needed for children in the formation of children’s independence. Based on data from the national statistical agency in 2014, the number of pre-school age children in indonesia was 28.022 people. This study aims to study the relationship of parenting parents with the level of personal hygiene independence in pre-school age children in the village of celegeh, barebali village, central lombok. This research is a descriptive correlational research with a cross sectional approach. The population in study amounted to 34 people. Sampling is done by using purposive sampling which amounts to 32 people, but in sampling there are exclusion criteria so that the total sample is 30 respondents. Research instruments using questionnaires. Data analysis techniques using the chi-square test α=0,05. The results showed that most of the patterns of adoption by respondents were 14 people (46,7%) authoritarian parenting, with 7 independent children (23,3%) and 7 non-independent children (23,3%). So it can be concluded there is a relationship between parenting parents with the level of personal hygiene independence in pre-school age children in the village of celegeh, barebali village, central lombok.